INFLUENCE OF ENVIRONMENTAL TEMPERATURE (COLD EXPOSURE) ON NASAL RESISTANCE - SANO, HAJIME (Nippon Jibi Inkoka Gakkai Kaiho, 1992)
Changes in nasal resistance were examined in 33 healthy subjects in order to investigate the physiological reactions of nasal mucosa to cold exposure. Each examinee was exposed to changes in room temperature from 25°C to 15°C with the same humidity in an artificial atmosphere chamber, regulated by an environmental control unit. Nasal resistance was measured by means of the active-anterior method using a rhinomanometer MPR-2200. The same experiments were repeated on different dates in all 18 subjects. The results can be summarized as follows. 1) The average value of nasal resistance significantly increased after room temperature was decreased from 25°C to 15°C. 2) Patterns of nasal resistance responses to cold exposure were classified into two types. One type was increased nasal resistance after cold exposure and the other was maintenance of resistance despite cold exposure. Each individual manifested a different pattern in experiments carried out on different dates. 3) The nasal resistance value in the chamber at 25°C was significantly higher in winter than in summer, and the increase in nasal resistance in response to cold exposure was significantly larger in summer than in winter. This result was assumed to be due to cold adaptation of the nasal mucosa in winter. 4) Heart rate decreased significantly with cold exposure. However, changes of heart rate in response to cold exposure did not correlate with changes in nasal resistance. No correlation between changes in nasal resistance in response to cold exposure and orthostatic loading, which was carried out after the cold exposure experiment, was detected. 5) A nasal cycle was observed in 7 (14%) of the 33 cases. In 6 of these total nasal resistance was maintained despite cold exposure.